2005
DOI: 10.1086/426468
|View full text |Cite
|
Sign up to set email alerts
|

Radiative Lifetime of thev = 0, 1 Levels of the \documentclass{aastex} \usepackage{amsbsy} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{bm} \usepackage{mathrsfs} \usepackage{pifont} \usepackage{stmaryrd} \usepackage{textcomp} \usepackage{portland,xspace} \usepackage{amsmath,amsxtra} \usepackage[OT2,OT1]{fontenc} \newcommand\cyr{ \renewcommand\rmdefault{wncyr} \renewcommand\sfdefault{wncyss} \renewcommand\encodingdefault{OT2} \normalfont \selectfont} \DeclareTextFontCommand{\textcyr}{\cyr}

Abstract: The time-delayed resonant two-photon ionization method has been used to measure the radiative lifetimes of the v ¼ 0 and 1 levels of the A 6 AE þ state of CrH, yielding values of 0:939 AE 0:019 and 1:027 AE 0:066 s, respectively (1 error limits). These measured lifetimes are about 16%-45% longer than those obtained in recent ab initio calculations, a result that is important for modeling of the atmospheric concentration of CrH in the class of substellar objects known as brown dwarfs. Based on these results, it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Recently Shin, Bruch & Morse (2005) have measured radiative lifetimes of the v = 0, 1 levels of A 6 Σ + state of CrH. These measured lifetimes are about 16–45 per cent longer that those obtained by Burrows et al (2002).…”
Section: Introductionmentioning
confidence: 89%
“…Recently Shin, Bruch & Morse (2005) have measured radiative lifetimes of the v = 0, 1 levels of A 6 Σ + state of CrH. These measured lifetimes are about 16–45 per cent longer that those obtained by Burrows et al (2002).…”
Section: Introductionmentioning
confidence: 89%
“…The instrument employed is identical to that used in our previous studies of CrH, 28 CrC, 29 and in vibronically resolved studies of CrCCH, CrCH 3 , and NiCH 3 . 8 Chromium acetylide was produced by pulsed laser ablation (Nd:YAG, 532 nm, ∼2 mJ/pulse, 5 ns pulse duration) of a pure chromium sample in the throat of a pulsed supersonic expansion of helium containing 3% methane.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…These were obtained using the time-delayed resonant two photon ionization method, as described in our article on the fluorescence lifetime of CrH. 28 A fit of the vibronic features to the formula…”
Section: B Vibronically Resolved Spectrummentioning
confidence: 99%
“…Many reports on CrH can be found in the literature. , Table includes the calculated and experimental results reported during the past decade, together with the present results. The latest study was carried out by Shin et al They observed the emission spectrum of the A 6 Σ + −X 6 Σ + transition and analyzed the results to obtain the spectroscopic parameters for both electronic states. As shown in Table , the present estimations of the spectroscopic parameters seem reasonable in comparison with the corresponding observations, except that the dissociation energy is a bit too low.…”
Section: Resultsmentioning
confidence: 99%